Penerapan Model Pembelajaran Kooperative Tipe Think Talk Write untuk Meningkatkan Hasil Belajar Menulis Karangan - Salwa (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
The problem faced in this study is the low learning of grade VI students at SD Negeri 007 Singkep, Singkep District, Lingga Regency in Indonesian Language Subjects for writing essays. This study aims to describe the application of the TTW type cooperative learning model (Think, Talk, Write) in improving student learning outcomes in Indonesian Language Subjects for writing essays in class VI SD Negeri 007 Singkep. This research uses classroom action research (CAR). The research was carried out on grade VI students of SD Negeri 007 Singkep in the second semester of the 2019/2020 academic year. Research using the TTW type cooperative learning model (Think, Talk, Write) can drastically improve student learning outcomes from cycle 1 as many as 4 students (80%), at the end of cycle II to 5 people (100%) and the class average score in the pre-cycle. 62.00 to 70.00 in the first cycle continued to increase in the second cycle to 80.00. Classically, in the second cycle, the completeness of class learning has reached 100%. The study concluded that the use of the TTW (Think, Talk, Write) type of cooperative learning model can improve student learning outcomes in Indonesian language subjects for writing essays.